HOW SOCIAL, BEHAVIORAL, AND POLICY FACTORS IMPACT WATER SATISFACTION AND MANAGEMENT IN URBAN AREAS - Haikal, Rafi; Firdaus, Thoriqi; Nabila, Siti Hilya; Chairunnisa, Rizqi Shafira (Journal of Environmental Science and Sustainable Development, 2025)
The issue of water management in Indonesia’s specific urban contexts, specifically in Surabaya as an industrial hub and Bali as a tourist destination, is of paramount importance due to its impact on public health and environmental sustainability. This study analyses water management and conservation factors by comparing two distinct urban areas. The research design employs Partial Least Squares Structural Equation Modelling (PLS-SEM), which involves a specialised approach for analysing the complex relationships between variables. The results of the analysis indicate that community attitudes in Surabaya, facilitated by infrastructure and technology, significantly predicts intention to perform (β=0.334, p<0.001) and water management satisfaction (β=0.409, p<0.001). In contrast, collaboration with the government enhances environmental constraints (β=0.285, p<0.003) and water management satisfaction (β=0.140, p<0.044). In Bali, where water management is based on traditional practices, community attitudes do not significantly affect water management satisfaction (β=0.095, p>0.431). Still, perceived norms reduce environmental constraints (β=-0.134, p<0.039) and enhance the intention to perform (β=0.189, p<0.037). The role of personal agency in Bali is more significant in reducing environmental constraints (β=-0.187, p<0.025) and increasing intention to perform (β=0.198, p<0.013). In contrast, in Surabaya, only personal agency was significant in increasing water management satisfaction (β=0.132, p<0.003). These findings suggest that Surabaya requires an integrative approach, while Bali must strengthen its locally based water management practices and enforce stricter regulations in the tourism sector to protect water resources.